The effect of enalapril on cardiac mechanics in the pediatric heart network infant single-ventricle trial: Insights using noninvasive pressure-volume loop analysis - Strelow, Jacob R.; Graham, Eric M.; Taylor, Carolyn L.; Atz, Andrew M.; Chowdhury, Shahryar M. (Annals of pediatric cardiology, 2025)
Patients with single-ventricle physiology who received enalapril in the Pediatric Heart Network Infant Single-ventricle Trial displayed no differences in heart failure outcomes compared to those who received a placebo. The objective of this study was to use noninvasive pressure-volume loop analysis to assess for differences in cardiac mechanics between the enalapril and placebo groups. Core-lab echocardiogram measures prior to superior cavopulmonary connection (SCPC) and post-SCPC at 14 months of age were obtained. End-systolic elastance (Ees), a measure of contractility, and arterial elastance (Ea), a measure of afterload, were calculated. Ventriculo-arterial coupling was expressed as Ea/Ees. Data from 150 patients were analyzed. There was no difference in Ees, Ea, or Ea/Ees between study groups at either time point. The failure of enalapril to improve heart failure outcomes in this cohort may have some association with its failure to improve cardiac mechanics in single-ventricle physiology.